Phase-2 Trial of an Intensified Conditioning Regimen for Allogeneic Hematopoietic Cell Transplant for Poor-Risk Leukemia - Stein, Anthony S. (2010)
Patients with poor-risk leukemia have a high relapse rate despite allogeneic transplant. We report on the phase II trial of an intensified allogeneic transplant regimen whose aim was tolerable toxicity and durable remission. Study patients (n=30) had unfavorable first remission cytogenetics, progression from myelodysplasia or active disease due to induction failure or relapse. Conditioning was intravenous busulfan, targeted to a first-dose plasma area under the curve (AUC) of 700–900 µM·min, VP-16 at 30 mg/kg of adjusted ideal body weight and fractionated total body irradiation (FTBI) at 1200 cGy in ten fractions. Graft-versus-host disease (GVHD) prophylaxis was cyclosporine A and mycophenolate mofetil. Regimen-related toxicities (Bearman) included grade 3 mucositis in 29 patients (97%) and grade 4 in one, grade 2–3 sinusoidal obstructive syndrome in 2 patients (7%), and grade 2–3 skin toxicity in 8 patients (27%). The 30- and 100-day transplant-related mortalities were 0% and 7% respectively. The median follow-up was 83.7 months (60.7–96.4) for surviving patients. The 5-yr overall and disease-free survival was 40% for all patients. Cumulative 5-yr relapse incidence was 23% and transplant-related mortality was 37%. We have shown promising overall survival and relapse incidence in these poor-risk patients, who typically have few curative options.